Substrate specificity of the deazaflavin-dependent nitroreductase from Mycobacterium tuberculosis responsible for the bioreductive activation of bicyclic nitroimidazoles - Gurumurthy, M. (2014)
10.1111/j.1742-4658.2011.08404.x